TAPBPR promotes editing of the HLA-B44 peptide repertoire, increasing the presentation of peptides containing a C-terminal tryptophan - Aflalo, Aure; Altenburg, Arwen F.; Wacker, Marcel; Khanfar, Esam; Bauer, Jens; Walz, Juliane S.; Boyle, Louise H. (Frontiers in Immunology, 2025)
Major histocompatibility complex class I (MHC-I) molecules play a key part in the adaptive immune response by presenting antigens to CD8+ T cells. The high degree of polymorphism in MHC-I leads to significant variation in their dependence on the components of the antigen processing and presentation pathway, such as the transporter associated with antigen processing (TAP) and tapasin, and their affinity for the peptide editor TAP-binding protein related (TAPBPR). Here, we investigated the influence of TAPBPR on the cell surface phenotype and peptide repertoire presented by two human leukocyte antigen (HLA) class I allotypes, HLA-B*44:02 and HLA-B*44:05, which are known to differ drastically in their dependence on tapasin. TAPBPR bound weakly to both HLA-B*44:02 and HLA-B*44:05. In contrast to tapasin depletion, the loss of TAPBPR has a limited effect on the cell surface expression of these two molecules. Analysis of the immunopeptidomes presented in the presence and absence of TAPBPR revealed that TAPBPR expression restricted the peptide repertoire presented on HLA-B*44:05, while it diversified the repertoire presented on HLA-B*44:02. Overall, TAPBPR improved the predicted affinity of the peptides displayed on both the HLA-B44 molecules. Furthermore, TAPBPR enhanced the presentation of peptides containing a C-terminal tryptophan residue. Our results show that TAPBPR can significantly impact the peptide repertoire of MHC-I molecules to which it binds weakly. Furthermore, this represents the first study that points to a role for TAPBPR in selecting a specific peptide sequence on MHC class I molecules.